Organic polymer crystal material based on hydrogen bond network as well as preparation method and application of organic polymer crystal material
By designing organic polymer crystal materials based on hydrogen bond network, the problems of easy dissolution and poor conductivity of organic electrode materials in electrolyte are solved, high conductivity and cyclic stability are achieved, and it is suitable for a variety of alkali metal ion batteries. Provides low-cost and environmentally friendly energy storage solutions.
Patent Information
- Application Number
- CN202411241838.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-05
AI Technical Summary
The existing organic electrode materials are easily dissolved in organic electrolytes and have poor conductivity, resulting in poor cycle stability and rate performance, limiting their application in metal ion batteries.
By designing organic polymer crystal materials based on hydrogen bond networks, using piperazine structure to connect benzenequinone monomers to expand the conjugated structure, forming a graphite-like layered structure, and using the coordinated coordination between carbonyl and piperazine to achieve reversibility of metal ions Store and enhance the stability of the material through intermolecular hydrogen bonding.
It realizes the high conductivity and excellent rate performance of organic electrode materials, improves cycle stability and capacity retention, is suitable for a variety of alkali metal ion batteries, and is characterized by low cost, environmental protection and large-scale production.
Smart Images

Figure CN119320493A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic positive electrode materials for batteries, and in particular relates to an organic polymer crystal material based on a hydrogen bond network and a preparation method and application thereof. Background Art
[0002] The rapid development of new energy electric vehicles, large-scale fixed energy storage equipment and national smart grids has put forward higher requirements on the energy density, cycle life and resource reserves of rechargeable secondary batteries. Metal-ion batteries have attracted widespread attention in recent years due to their high energy density. However, traditional metal-ion batteries are often based on inorganic electrode materials, such as transition metal oxides and graphite, and usually show low actual production capacity or rely on scarce natural resources. In contrast, organic electrode materials have the advantages of abundant sources, high specific capacity, designable structure and green environmental protection. In addition, organic materials are generally not limited by ion selection, and it is feasible to apply the same organic molecules in various metal-ion batteries. This makes organic secondary batteries have broad application prospects in the field of large-scale energy storage.
[0003] However, organic electrode materials usually dissolve in organic electrolytes, and their capacity decay is serious during the cycle. In addition, their intrinsic conductivity is poor, which limits their rate performance. If the cycle stability and rate performance of organic electrode materials can be effectively improved, their high capacity will be expected to become candidate materials for metal ion batteries. In response to the solubility problem of organic molecules, reported solutions include salt formation, polymerization, porous matrix loading, etc., but these methods still have some limitations. Ordinary polymerization strategies will introduce inactive components and reduce specific capacity; at the same time, polymerization easily leads to molecular chain entanglement, which is not conducive to the full exposure of active sites. From the perspective of molecular structure design, extending the conjugated structure and improving the interaction between molecules are also effective strategies to solve the problems of organic electrode materials being easily soluble in organic electrolytes and having poor conductivity. Therefore, in response to the problems of easy solubility and poor conductivity of organic compounds, it is of great significance to design and synthesize organic electrode materials suitable for reversible ion embedding and extraction through function-oriented molecular structure design strategies. Summary of the invention
[0004] In view of the defects of the prior art and the need for improvement, the present invention provides an organic polymer crystalline material based on a hydrogen bond network, which is used in alkali metal ion batteries. Its purpose is to solve the problems of poor conductivity, solubility and low active site utilization of polymer electrode materials in existing organic electrode materials.
[0005] To achieve the above-mentioned purpose, the first aspect of the present invention provides an organic polymer crystal material based on a hydrogen bond network, which is used as an electrode material for alkali metal ion batteries. The organic electrode material uses unsaturated carbonyl groups as redox active sites, and utilizes the synergistic coordination between carbonyl groups and N and O in piperazine and metal ions to form a complex, thereby achieving reversible storage of metal ions. It is characterized in that the conjugated structure is extended by connecting the polymerized monomer benzoquinone through the piperazine structure to achieve rigid polymerization, wherein the NH bond on the piperazine unit and the C=O on the benzoquinone unit can form an intermolecular hydrogen bond, connecting the polymer molecular chain to achieve two-dimensional expansion, and finally forming a graphite-like layered structure.
[0006] The second aspect of the present invention provides a method for preparing the above-mentioned organic polymer crystal material based on the hydrogen bond network, and the organic electrode material preparation method comprises the following steps: dispersing the raw materials tetraaminobenzoquinone and tetrachlorobenzoquinone in a solvent N,N-dimethylformamide, and after reflux reaction under an argon atmosphere, filtering, washing and drying to obtain an organic polymer crystal material based on the hydrogen bond network.
[0007] Furthermore, in the preparation method of the present invention, the amount of raw materials used is: 1 mmol of tetrachloro-p-benzoquinone and 4 mmol of tetraamino-p-benzoquinone are added to 50 ml of N,N-dimethylformamide.
[0008] Furthermore, in the preparation method of the present invention, the reflux reaction is carried out under argon atmosphere for 12 hours.
[0009] Furthermore, in the preparation method of the present invention, after suction filtration, the filter cake is washed with N,N-dimethylformamide and methanol until it becomes colorless and then vacuum dried to obtain an organic polymer crystal material.
[0010] The present invention also provides an alkali metal ion battery, characterized in that the electrode material of one electrode or multiple electrodes is the organic electrode material as described above.
[0011] Furthermore, the alkali metal is lithium, sodium, or potassium.
[0012] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects:
[0013] (1) The current requirements for the energy density, cycle life and resource reserves of rechargeable secondary batteries have been raised. The present invention provides an organic polymer crystal material based on a hydrogen bond network for alkali metal ion batteries. The conjugated structure is extended by connecting the polymer monomer benzoquinone through a piperazine structure to achieve rigid polymerization, wherein the NH bond on the piperazine unit and the C=O on the benzoquinone unit can form an intermolecular hydrogen bond, connecting the polymer molecular chain to achieve two-dimensional expansion, and finally forming a graphite-like layered structure. It uses unsaturated carbonyl groups as redox active sites, and utilizes the synergistic coordination of carbonyl groups and N, O in piperazine with metal ions to form complexes to achieve reversible storage of metal ions. The organic electrode material has a flexible structure and can accommodate the embedding / ejection of ions of different radii, and is suitable for a variety of alkali metal ion batteries.
[0014] (2) The organic polymer crystal material based on the hydrogen bond network provided by the present invention has an intramolecular π-conjugated structure extended by a piperazine structure, which is beneficial to the rapid transmission of electrons and has excellent conductivity; the molecules interact with each other through π-π to form an ordered arrangement of a graphite-like structure, which is beneficial to the rapid transfer of ions and has excellent rate performance.
[0015] (3) The organic electrode material provided by the present invention utilizes piperazine as an active site connecting unit and introduces intermolecular hydrogen bonding interactions, which is beneficial to stabilizing the molecular structure, solving the problem of dissolution of the organic electrode material in the electrolyte and the problem of entanglement of the polymer molecular chains, and improving the cycle stability of the battery.
[0016] (4) The organic electrode material provided by the present invention has low cost, simple experimental operation, short reaction time, mild preparation conditions, is green and environmentally friendly, recyclable, and can be synthesized on a large scale. This provides a new choice and new direction for the use of green, environmentally friendly, low-cost, and large-scale producible organic materials in the energy storage field, and has good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A schematic diagram of the molecular structure of Example 1 provided by the present invention;
[0018] Figure 2 The infrared spectrum of Example 1 provided by the present invention;
[0019] Figure 3 The XRD spectrum of Example 1 provided by the present invention;
[0020] Figure 4 The first ten charge and discharge curves of the sodium battery of Example 2 provided by the present invention;
[0021] Figure 5 This is a sodium electrical cycle performance diagram of Example 2 provided by the present invention;
[0022] Figure 6 This is a sodium electric rate performance diagram of Example 2 provided by the present invention;
[0023] Figure 7 The lithium battery charge and discharge curve of Example 2 provided by the present invention;
[0024] Figure 8 The electronic conductivity of Example 1 and Comparative Example 1 provided by the present invention;
[0025] Fig. 9 This is a diagram of the sodium electrical cycle performance of Comparative Example 1 provided by the present invention. DETAILED DESCRIPTION
[0026] The present invention will be further explained below through the accompanying drawings and specific examples. The following examples are only used as an illustration and should not be understood as limiting the scope of the present invention. The protection scope of the present invention is not limited to the following embodiments.
[0027] Example 1
[0028] A design and preparation method of an organic polymer crystal material based on a hydrogen bond network, wherein the chemical formula of the positive electrode material is (C 6 H 2 N 2 O 2 ) n The organic electrode material uses unsaturated carbonyl groups as redox active sites, and utilizes the synergistic coordination between carbonyl groups and N and O in piperazine and metal ions to form complexes to achieve reversible storage of metal ions. Figure 1 The molecular structure diagram of Example 1. The organic polymer crystal material of the present invention uses a piperazine structure to connect the polymerized monomer benzoquinone to extend the conjugated structure and realize rigid polymerization, wherein the NH bond on the piperazine unit and the C=O on the benzoquinone unit can form an intermolecular hydrogen bond, connecting the polymer molecular chain to achieve two-dimensional expansion, and finally forming a graphite-like layered structure.
[0029] The above-mentioned organic electrode material, its preparation method comprises the following steps:
[0030] Weigh 1 mmol of tetrachloro-p-benzoquinone and 4 mmol of tetraamino-p-benzoquinone, add 50 ml of N,N-dimethylformamide and reflux under an inert atmosphere for 12 h. Cool to room temperature and filter. Wash the filter cake with N,N-dimethylformamide and methanol until it becomes colorless and then vacuum dry to obtain dark green solid PTABQ. Figure 2 and Figure 3 They are the infrared spectrum and XRD spectrum of Example 1 respectively.
[0031] Example 2
[0032] The present invention also provides an application of the electrode material. The organic polymer crystal material has a π-conjugated structure extended by a piperazine structure in the molecule, which is conducive to the rapid transmission of electrons and has excellent conductivity. The molecules form an ordered arrangement of a graphite-like structure through π-π interactions, which is conducive to the rapid transfer of ions and has excellent rate performance. The organic electrode material has a flexible structure and can accommodate the insertion / extraction of ions of different radii. It can be used as an electrode material for alkali metal ion batteries and is suitable for a variety of alkali metal ion batteries.
[0033] Based on the above description, the present invention further provides an alkali metal ion battery, comprising the electrode material as described above, preferably, the alkali metal includes: lithium, sodium, potassium.
[0034] The preparation method of the alkali metal ion battery in this embodiment is to grind and mix the PTABQ described in Example 1 with the conductive carbon (SuperP) and the binder (PVDF) in a mass ratio of 5:4:1, transfer them to a homogenizing box, and add an appropriate amount of N-methylpyrrolidone. After being fully mixed in the homogenizer, the slurry is coated on aluminum foil with a scraper, first dried in a 60°C forced air oven for 6 hours, and then dried in a 100°C vacuum oven for 12 hours. A disc with a diameter of 10 mm is obtained by a tabletting machine.
[0035] In an argon glove box, 1.0 M NaPF 6 DEGDME was used as the electrolyte, Celgard 2400 was used as the separator, and the PTABQ positive electrode and the metallic sodium negative electrode were assembled into a button cell for testing the electrochemical performance of the sodium battery.
[0036] In an argon glove box, using 1.0M LiTFSIDOL / DME as the electrolyte and Celgard 2400 as the separator, the PTABQ positive electrode and the metallic lithium negative electrode were assembled into a button cell for testing the electrochemical performance of the lithium battery.
[0037] Attached Figure 4 Description: PTABQ material can produce up to 350mAh g -1 The specific capacity and the average discharge voltage are about 2V. It has good cycle reversibility and stability. There is almost no capacity decay in the first ten cycles, and it has reversible sodium ion storage capacity.
[0038] Attached Figure 5 Description: PTABQ material has excellent cycle stability. -1 The capacity retention rate is still 94.6% after 200 cycles at the current density. This is due to the structural characteristics of PTABQ, which makes it have good dissolution inertness and good stability during the charge and discharge cycle.
[0039] Attached Figure 6Description: PTABQ has excellent rate performance, up to 5Ag -1 It can still deliver nearly 200mAh g -1 The capacity is attributed to the enhanced conductivity of the material due to the extended conjugated structure, and the layered structure provides a fast ion transport channel.
[0040] Attached Figure 7 Note: PTABQ material also has reversible lithium ion storage capacity in lithium batteries, with a capacity of 350 mAhg -1 The specific capacity is about 2.4V and the discharge medium voltage is about 2.4V, which shows that the PTABQ positive electrode is suitable for various alkali metal ion batteries.
[0041] Comparative Example 1
[0042] A small molecule organic positive electrode material, a polymerized monomer 1,2,4,5-tetraaminobenzoquinone (TABQ) of a PTABQ material.
[0043] TABQ was prepared into a positive electrode sheet in the manner described in Example 2. In an argon glove box, 1.0 M NaPF 6 DEGDME was used as the electrolyte, Celgard 2400 was used as the separator, and the TABQ positive electrode and the metallic sodium negative electrode were assembled into a button cell for electrochemical performance testing.
[0044] Figure 8 The electronic conductivity of the material in Example 1 is compared with that of the material in Comparative Example 1. The conductivity of the material in Example 1 is two orders of magnitude higher than that of the material in Comparative Example 1, indicating that the use of piperazine as an active site connecting unit to expand the conjugated structure in the present invention improves the conductivity of the material. Fig. 9 This is the long cycle performance diagram of Comparative Example 1. -1 After 100 cycles at the current density of 500 mA g, the capacity retention rate of Example 2 was only 74%. -1 The capacity retention rate after 200 cycles at the current density is 94.6%. This is due to the use of piperazine as an active site connecting unit proposed in the present invention, the introduction of intermolecular hydrogen bond interactions, the stabilization of the molecular structure, and the solution of the problem of dissolution of organic electrode materials in the electrolyte, thereby improving the cycle stability of the battery.
[0045] The organic electrode material provided by the present invention uses piperazine as an active site connection unit, introduces intermolecular hydrogen bond interactions, is conducive to stabilizing the molecular structure, solves the problem of organic electrode material dissolving in electrolyte and the problem of polymer molecular chain entanglement, and improves the cycle stability of the battery. At the same time, the organic electrode material has low cost, simple experimental operation, short reaction time, mild preparation conditions, green and environmentally friendly, recyclable, and can be synthesized on a large scale, which provides a new choice and new direction for the use of green, low-cost, and large-scale production organic materials in the field of energy storage, and has good commercial prospects.
Claims
1. An organic polymer crystal material based on a hydrogen bond network, characterized in that: The chemical formula of the organic polymer crystal material is (C6H2N2O2) n This material is commonly used in alkali metal ion batteries. The organic electrode material uses unsaturated carbonyl groups as redox active sites and utilizes the synergistic coordination of carbonyl groups and N, O in piperazine with metal ions to form complexes to achieve reversible storage of metal ions.
2. The organic polymer crystal material according to claim 1, characterized in that: The conjugated structure is extended by connecting the polymerized monomer benzoquinone through the piperazine structure to achieve rigid polymerization, wherein the NH bond on the piperazine unit and the C=O on the benzoquinone unit can form an intermolecular hydrogen bond, connecting the polymer molecular chain to achieve two-dimensional expansion, and finally forming a graphite-like layered structure.
3. The method for preparing the organic polymer crystalline material based on the hydrogen bond network according to claim 1 or 2, characterized in that The method comprises the following steps: dispersing raw materials tetraamino-p-benzoquinone and tetrachloro-p-benzoquinone in a solvent N,N-dimethylformamide, subjecting the materials to reflux reaction under an argon atmosphere, and then filtering, washing and drying to obtain an organic polymer crystal material based on a hydrogen bond network.
4. The preparation method according to claim 3, characterized in that: The dosage of the raw materials is as follows: add 1 mmol of tetrachloro-p-benzoquinone and 4 mmol of tetraamino-p-benzoquinone to 50 ml of N,N-dimethylformamide.
5. The preparation method according to claim 3, characterized in that: The reaction was refluxed for 12 h under argon atmosphere.
6. The preparation method according to claim 3, characterized in that: After filtration, the filter cake is washed with N,N-dimethylformamide and methanol until it becomes colorless and then dried in vacuo to obtain an organic polymer crystal material.
7. An alkali metal ion battery, characterized in that: The electrode material of one or more electrodes is the organic polymer crystal material as claimed in claim 1 or 2.
8. An alkali metal ion battery according to claim 7, characterized in that: The alkali metal is lithium, sodium, or potassium.
Citation Information
Patent Citations
General organic electrode material for alkali metal ion battery and application of general organic electrode material
CN114204020A
Conjugated quinone azine organic electrode material and preparation method and application thereof
CN114497547A
Polymer containing pyrazine-benzoquinone structure and application of polymer in lithium ion / aqueous zinc ion battery
CN114920930A
Organic trapezoidal polymer, preparation method thereof and application of organic trapezoidal polymer in lithium ion battery
CN115073731A
Polymer, electrode active substance and secondary battery
WO2020084828A1